Non-clinical Pharmacology of YTX-7739: a Clinical Stage Stearoyl-CoA Desaturase Inhibitor Being Developed for Parkinson’s Disease - Daniel F. Tardiff; Matthew Lucas; Iwona Wrona; Belle Chang; Chee Yeun Chung; Bertrand Le Bourdonnec; Kenneth J. Rhodes; Robert H. Scannevin (Molecular Neurobiology, 2022)
Summary Stearoyl-CoA desaturase (SCD) is a potential therapeutic target for Parkinson’s and related neurodegenerative diseases. SCD inhibition ameliorates neuronal toxicity caused by aberrant α-synuclein, a lipid-binding protein implicated in Parkinson’s disease. Its inhibition depletes monounsaturated fatty acids, which may modulate α-synuclein conformations and membrane interactions. Herein, we characterize the pharmacokinetic and pharmacodynamic properties of YTX-7739, a clinical-stage SCD inhibitor. Administration of YTX-7739 to rats and monkeys for 15 days caused a dose-dependent increase in YTX-7739 concentrations that were well-tolerated and associated with concentration-dependent reductions in the fatty acid desaturation index (FADI), the ratio of monounsaturated to saturated fatty acids. An approximate 50% maximal reduction in the carbon-16 desaturation index was observed in the brain, with comparable responses in the plasma and skin. A study with a diet supplemented in SCD products indicates that changes in brain C16 desaturation were due to local SCD inhibition, rather than to changes in systemic fatty acids that reach the brain. Assessment of pharmacodynamic response onset and reversibility kinetics indicated that approximately 7 days of dosing were required to achieve maximal responses, which persisted for at least 2 days after cessation of dosing. YTX-7739 thus achieved sufficient concentrations in the brain to inhibit SCD and produce pharmacodynamic responses that were well-tolerated in rats and monkeys. These results provide a framework for evaluating YTX-7739 pharmacology clinically as a disease-modifying therapy to treat synucleinopathies.